High Notch1 expression affects chemosensitivity of head and neck squamous cell carcinoma to paclitaxel and cisplatin treatment - Zuping Zhang (Biomedicine & Pharmacotherapy, 2019)
Background: Notch1 expression has been reported to be associated with chemotherapy resistance and poor prognosis, but the role of Notch1 in head and neck squamous cell carcinoma (HNSCC) sensitivity to anticancer drugs remains unclear. The aim of this study was to evaluate HNSCC sensitivity to paclitaxel and cisplatin in vitro and the chemotherapeutic response of HNSCC to these two drugs in vivo. Methods: We used immunohistochemistry to assess Notch1 expression in fresh HNSCC samples treated by PF (cisplatin+5- fluorouracil) and TPF (paclitaxel + cisplatin+5- fluorouracil). We also assessed the sensitivity of two HNSCC cell lines to the Notch1 inhibitor of N-[N-(3,5-difluorophenacetyl)-L-alanyl]-S-phenylglycine t-butyl ester (DAPT). The overall and progression-free survival were assessed. Results: High Notch1 expression was significantly associated with paclitaxel resistance (P < 0.01). DAPT increased sensitivity to paclitaxel and cisplatin in vitro (P < 0.05). Compared with patients with Notch1 expression, patients without Notch1 expression were more likely to have a response to neoadjuvant chemotherapy with PF (P < 0.01) or TPF (P < 0.01) and had significantly better overall survival (P < 0.05) and progression-free survival (P < 0.05). Among patients without Notch1 expression (but not among patients with Notch1 expression), those who received TPF had significantly better survival than those who received PF (P < 0.05). Conclusion: Taken together, our findings may provide some evidence to partially support the predictive value of Notch1 expression in the therapeutic response to paclitaxel and cisplatin.